2003
DOI: 10.1136/heart.89.4.417
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of statin prescribing 1994-2001: a case of agism but not of sexism?

Abstract: Objective: To study trends in the use of lipid lowering drugs in the UK, and to assess which patient factors influence prescribing. Methods: Routinely collected computerised medical data were analysed from 142 general practices across England and Wales that provide data for the Doctors' Independent Network database. Subjects included were people aged 35 years or more with treated ischaemic heart disease, averaging annually over 30 000. The temporal trend from 1994 to 2001 in prescription of lipid lowering drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
91
4
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 14 publications
20
91
4
6
Order By: Relevance
“…As expected and consistent with previous studies, 13,15,28 patients with dyslipidemia before CHD hospitalization and those hospitalized because of AMI were more likely to start statin therapy after discharge. Although the presence of baseline diabetes and hypertension was significantly associated with a lower likelihood of initiation of statins in univariate analysis, the significance disappeared after controlling for other factors, indicating that they were not independent factors and the lower observed rate of statin use in patients with diabetes and hypertension might be confounded by other factors.…”
Section: ■■ Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…As expected and consistent with previous studies, 13,15,28 patients with dyslipidemia before CHD hospitalization and those hospitalized because of AMI were more likely to start statin therapy after discharge. Although the presence of baseline diabetes and hypertension was significantly associated with a lower likelihood of initiation of statins in univariate analysis, the significance disappeared after controlling for other factors, indicating that they were not independent factors and the lower observed rate of statin use in patients with diabetes and hypertension might be confounded by other factors.…”
Section: ■■ Discussionsupporting
confidence: 79%
“…41,42 Regarding gender, previous studies have suggested that men are more likely to receive a statin than women, but the difference disappears once age differences and other factors are controlled. 15,41 In contrast, our findings show a gender bias regarding initiation of statin therapy after discharge from CHD hospitalization after adjustment for other factors. The discrepancy with previous literature might be because of the difference in study populations.…”
Section: ■■ Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Ecological analyses of hospital procedures have shown lower rates of angiography and revascularisation in practices with high deprivation scores (Hippsley-Cox & Pringle, 2000). Practice-based data show that men with heart disease are more likely to receive lipid-lowering drugs than women, with a greater gender bias among the 45-54 than older age groups (Hippisley-Cox, Pringle, Crown, Meal & Wynn, 2001), while DeWilde, Carey, Bremner, Richards, Hilton & Cook (2003) found lower prescription of lipid lowering drugs with increased age, but no sex difference after adjustment for disease severity. A population-based survey in Boston of patients seeking care for heart symptoms found lower cardiologist referral rates among blacks, and white women received less CHD-related treatment than men (Crawford, McGraw, Smith, McKinlay & Pierson, 1994;McKinlay, 1996).…”
Section: Processing Chd Patients In Primary Carementioning
confidence: 99%